The TOR Pathway at the Neuromuscular Junction: More Than a Metabolic Player? - Castets, Perrine; Ham, Daniel J.; Rüegg, Markus A. (Frontiers in Molecular Neuroscience, 2020)
The neuromuscular junction (NMJ) is the chemical synapse connecting motor neurons and skeletal muscle fibers. NMJs allow all voluntary movements, and ensure vital functions like breathing. Changes in the structure and function of NMJs are hallmarks of numerous pathological conditions that affect muscle function including sarcopenia, the age-related loss of muscle mass and function. However, the molecular mechanisms leading to the morphological and functional perturbations in the pre- and post-synaptic compartments of the NMJ remain poorly understood. Here, we discuss the role of the metabolic pathway associated to the kinase TOR (Target of Rapamycin) in the development, maintenance and alterations of the NMJ. This is of particular interest as the TOR pathway has been implicated in aging, but its role at the NMJ is still ill-defined. We highlight the respective functions of the two TOR-associated complexes, TORC1 and TORC2, and discuss the role of localized protein synthesis and autophagy regulation in motor neuron terminals and sub-synaptic regions of muscle fibers and their possible effects on NMJ maintenance.